Use of bidirectional DC-DC Buck Boost Converter in Distributed Energy Resources (DER) - Tajwar, Fahim; Lethe, Tasneem Nawreen; Khan, Shahriar Usman; Sardar, Atiqur Rahman (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.